Translating the neologism: comparative study of the novel Zazie in the Metro by Raymond Queneau and its Bulgarian translation (Colloquia Comparativa Litterarum, 2025)
The study seeks to determine the level of adequacy of the transfer into Bulgarian of the neologisms coined by Raymond Queneau in the novel Zazie in the Metro (1959). To this end, we examine the translation strategies implemented in Зази в метрото (2001). Starting from the assumption that, while translation is possible, the degree of translatability of a neologism is variable, we evaluate the relevance of the equivalents proposed by the translator.
Keywords: adequacy; equivalence; neologism; Raymond Queneau; translation